(untitled) (Global Journal of Management and Business Research, 2018)
The main objective of this study is to through perceptual econometric analysis explore the relationship between macroeconomic performance proxied by macroeconomic stability and financial performance of the Nigerian banking Industry The study employed Generalised Method of Moments technique in a firm-level analysis of 120 bank branches and 2400 customers in Nigeria It was revealed that at the 1 significance level macroeconomic performance positively impacts on the financial performance of the Nigerian banking industry It was also found that managers sex and employment status significantly predict performance Female managers seemed to be more profitable than their male counterparts and the higher the employment status of the bank managers the more their abilities to drive profitability of their banks Policies aimed at stabilizing the economy would invariably enhance Nigerian banking industry s growth and stability